2019
DOI: 10.1136/annrheumdis-2018-214469
|View full text |Cite
|
Sign up to set email alerts
|

Reducing arthritis fatigue impact: two-year randomised controlled trial of cognitive behavioural approaches by rheumatology teams (RAFT)

Abstract: ObjectivesTo see if a group course delivered by rheumatology teams using cognitive-behavioural approaches, plus usual care, reduced RA fatigue impact more than usual care alone.MethodsMulticentre, 2-year randomised controlled trial in RA adults (fatigue severity>6/10, no recent major medication changes). RAFT (Reducing Arthritis Fatigue: clinical Teams using CB approaches) comprises seven sessions, codelivered by pairs of trained rheumatology occupational therapists/nurses. Usual care was Arthritis Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 44 publications
1
87
0
Order By: Relevance
“…The key clinical findings from the RAFT programme trial presented here have been previously published. 65…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key clinical findings from the RAFT programme trial presented here have been previously published. 65…”
Section: Resultsmentioning
confidence: 99%
“…The key discussion points for the clinical and qualitative evaluations have previously been published. 65…”
Section: Overall Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way of reducing the costs associated with ACT is to reduce the length of training sessions and/or train rheumatology health professionals to deliver ACT treatments, as has been done with other psychological treatments (Hewlett et al, 2019). Additionally, research exploring how ACT treatment works would enable researchers to fine-tune ACT interventions and provide more effective treatment in a shorter time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, evidence suggests, for example, that community-based exercise programmes exert a positive (although modest) effect on anxiety36 37 and depression38 among patients with arthritis and other rheumatic conditions. A recent trial demonstrated that group-based cognitive behavioural therapy delivered within rheumatology teams reduced the impact of fatigue in patients with RA 39. Such therapy aims to reduce the impact of, for example, fatigue and widespread pain rather than improving symptoms per se, and not all patients are willing to engage with them.…”
Section: Discussionmentioning
confidence: 99%